ANALISIS ABC DALAM PERENCANAAN OBAT ANTIBIOTIK DI RUMAH SAKIT ORTOPEDI SURAKARTA - Tina Hari Yanti; Yeni Farida (Universitas Sebelas Maret, 2016)
Planning of drug is an attempt determination of the type of drug, quantity and quality of medicines as needed. Antibiotics are used as primary therapy in cases of bacterial infection, so it needs a good planning for control the supplies. This study aims to classify antibiotics using ABC analysis to help the control of antibiotic drugs at Pharmacy Instalation of Prof. Dr. R. Soeharso Orthopedy Hospital Surakarta.The design of this study is non-experimental research with descriptive analysis by using quantitative data. Data was analyzed using Microsoft Excel 2007. Data was obtained from prescriptions that contain antibiotic drugs at Pharmacy Instalation of Prof. Dr. R. Soeharso Orthopedy Hospital Surakarta during 2013. Data was analyzed using ABC method. The data classified by usingABC method showed that out of 100 antibiotic drug items, 9 (9%) are categorized as group A, 13 (13%) are categorized as group B, and 78 (78%) are categorized as group C.